Pedagogical bases of Ishakhon Ibrat's scientific views on Science - Nurmatova Madina Odiljon qizi (International Journal on Orange Technologies, 2021)
The article describes the life of Ishaq Khan Ibrat, one of the great representatives of modern literature. The scientist's pedagogical views on science are revealed based on scientific evidence